Students from all Layers of Society. Study Grants, Parents and the Education of their Children, 1815-2015 - Wouter Marchand (Historical Life Course Studies)
This paper investigates how the system of government grants affected individual life chances for students in the Netherlands from 1815 to today, focusing on the accessibility of academic education and opportunities for social mobility. Study grants for adolescents from lower class or low-income families can promote upward intergenerational social mobility, since they remove the financial barriers of continuing education and can lead to occupations of a higher standing. By investigating the social background and careers of a sample of grant students compared to the overall student populations, this paper uncovers to what extent study grants had an effect on an individual and societal scale. During the two centuries under study the aims and size of the grant system changed, causing concerns about the effectiveness of the grants. In the entire nineteenth century grants for university students were restricted to those already enrolled, minimizing the appeal for newcomers from low-income families. The limited number of grants available prevented the system from influencing the composition of the student population fundamentally. However, this changed when the grant system was extended in 1919, and again after 1945 when grant allocation was connected to parental income level. The rapid increase of educational participation and connected democratisation from the 1960s made the grant system influential, however costly. The grant system has been a subject of ongoing political debate during the last few decades, since the grants’ effect on upward social mobility has been called into question.